A System of international comparisons of gross product and purchasing power - Kravis, Irving B.; United Nations International Comparison Project (Baltimore : Published for World Bank by Johns Hopkins University Press, 1975)
The focus of this book was to fill the important gap in international statistics by developing detailed intercountry comparisons for gross domestic product and the purchasing power of currencies.
At head of title: United Nations International Comparison Project: phase one.
Includes bibliographical references and index.
osa;05/10/17
Loans
Keywords: Income; Gross national product; Purchasing power